-3/[(x-1)(x-1)]
2x/[(x-4)(x-1)]
it has to have (x-4) and two (x-1)s
Find the LCD for the following rational expressions.
(-3 / x^2 - 2x + 1) (2x / x^2 - 5x + 4)
a)( x - 1) (x - 4)
b)(x - 1)^3 (x - 4)
c)(x - 1) (x + 4)
d)(x - 1)^2 (x - 4)
2 answers
(-3/(X^2-2X+1))+(2X/(X^2-5X+4)
In order to find an LCD, we need 2 or
more fractions separated by a plus or
minus sign. so I added a plus sign.
CD=(X^2-2X+1)(X^2-5X+4)=(X-1)^2(X-1)(X-4).This product is a CD but not the LCD. To get LCD, reduce the squared factor to (X-1), LCD=(X-1)(X-1)(X-4)=
(X-1)^2(X-4).
In order to find an LCD, we need 2 or
more fractions separated by a plus or
minus sign. so I added a plus sign.
CD=(X^2-2X+1)(X^2-5X+4)=(X-1)^2(X-1)(X-4).This product is a CD but not the LCD. To get LCD, reduce the squared factor to (X-1), LCD=(X-1)(X-1)(X-4)=
(X-1)^2(X-4).